Allomorphs in Meeteilon (Manipuri) Morphology - Devi, Heisnam Kenny; Singh, L. Sarbajit (Nepalese Linguistics, 2022)
The paper is strictly based on the study of the distribution of various allomorphs in Meeteilon morphology in order to study the morphosyntactic nature of the word. Allomorphs can be distributed phonologically, morphologically and lexically. However, for Meeteilon there is only phonologically conditioned allomorphs. The classification of these allomorphs will be helpful in the segmentation of morphemes, morpheme identification, parts of speech tagging and other fields related to natural language processing by setting the phonological rule which accounts morphological alternation. Finally, an introduction to optimality theory approach has been applied in the final devoicing of the syllable.